Prosedur Penataan Dokumen Perizinan Lingkungan sebagai Upaya Pemeliharaan Arsip Dinamis Inaktif pada Dinas Lingkungan Hidup Kota Surabaya - Laksmita Triadewi Mounty; Mahmudatul Himmah (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
The Surabaya City Environment Agency is one of the local government agencies that has the authority to manage and protect environmental quality. After the merger with the Hygiene and Green Open Space Office, this agency faces serious challenges, especially in terms of archive management. Several times the process of moving archives has resulted in obstacles in the arrangement of inactive dynamic archives. This condition not only causes difficulties in the process of retrieving archives, but also has an impact on physical damage and the potential for loss of important documents, especially high-value environmental permit documents. This research aims to develop a more systematic procedure for structuring inactive dynamic archives so that it can facilitate the activities of maintaining, searching, and rediscovering archives when needed. The research method used is action research with data collection techniques in the form of interviews, observations, documentation, and questionnaire distribution. The research respondents consisted of employees of the Environmental Planning and Supervision Division and archivists in the Secretariat Division. The collected data was then analyzed descriptively using the Likert scale to measure perception and the Accuracy Score to assess the effectiveness of archival recollection. The results of the study showed that the inactive dynamic archive arrangement procedure applied was assessed in accordance with the needs of the organization. The level of effectiveness measured through the Precision Score reached a value of 0.57%, which means that the archive can be recovered well. This confirms that the procedures prepared are able to improve the quality of archive management and support administrative services within the Surabaya Environment Office.